Green technology of liquid biphasic flotation for enzyme recovery utilizing recycling surfactant and sorbitol - Sankaran, Revathy; Show, Pau Loke; Yap, Yee Jiun; Tao, Yang; Ling, Tau Chuan; Tomohisa, Katsuda (Springer, 2018)
Liquid biphasic flotation (LBF) system has been recognized as an efficient, green, economically sustainable and biocompatible technique for biomolecules separation and purification. The main drawbacks of the conventional process of biomolecules separation are expensive production cost, utilization of phase components that are inefficiently recycled and global pollution due to high chemical consumption and wastage. In this paper, a novel approach of LBF system for lipase recovery utilizing recycling phase components comprising surfactant and xylitol was investigated. The scope of this study focuses on pollution prevention as well as clean and environmentally friendly process for enzyme extraction via LBF. The green process proposed in this study uses phase-forming components that have recovery and recycling abilities for minimal use of chemicals for enzyme extraction. This novel method utilized Triton X-100 and xylitol for lipase extraction from Burkholderia cepacia. A few parameters were optimized to obtain high lipase separation efficiency and yield. Based on the ideal conditions of LBF, the average lipase separation efficiency and yield are 86.46 and 87.49%, correspondingly. Phase components recycling were proposed in order to reduce the chemicals consumption in LBF system. Upscaling of the recycling study exhibited consistent result with the laboratory scale. It was found that 97.20 and 98.67% of Triton X-100 and xylitol were recovered after five times of recycling and that a total of 75.87% of lipase separation efficiency was obtained. Recovery and recycling of phase components in the extraction process are established as the principal green chemistry method, which yields high separation efficiency and is economically feasible on an industrial scale.